Regulating Digital Platforms in Times of Democratic Crisis – What is Next for Germany and the EU? - Clara Iglesias Keller; Jakob Ohme; Lukas Seiling; Christoph Neuberger (Weizenbaum-Institut, 2025)
This paper examines recent changes in the content moderation practices of major social media companies. Digital platforms have become a defining feature of contemporary societies. As their infrastructures increasingly mediate commercial activity, political organization, cultural life, and more, the retraction of measures meant to uphold standards and trust in their influence over online speech raises significant concerns. This paper briefly analyzes these developments in the context of ongoing processes of democratic erosion, particularly in the U.S. The goal is to foster future research and public debate by offering key insights into the implications of the current scenario for Germany and the European Union.
Keywords: 330; European Union; Digital Platforms; Regulation; Policy; Social Media; X; Meta